Digital Transformation of Archival Management through the SRIKANDI Application: A Study at the Banda Aceh Library and Archives Office - Cut Aulia Suci Ranosa; Taufik Taufik; Delfi Suganda (Master of Public Administration FISIPOL Universitas Negeri Surabaya, 2026)
This study examines the digital transformation of archival management through the implementation of the SRIKANDI application at the Banda Aceh Library and Archives Office. The research is motivated by challenges in manual archival systems, including document loss risks, limited storage capacity, slow information retrieval, and low efficiency in public service delivery. This study adopts a qualitative descriptive approach, with data collected through observation, interviews, documentation, and audiovisual materials. The findings indicate that the implementation of SRIKANDI has significantly improved the efficiency, accessibility, and security of archival management by enabling digital creation, storage, retrieval, and distribution of official documents. The transformation is supported by three key dimensions: technology, organizational support, and human resources. However, several challenges remain, particularly related to technical disruptions such as instability of the national server used collectively across institutions. The study concludes that while SRIKANDI has contributed to modernizing archival governance and enhancing public service quality, further improvements in technical infrastructure, user capacity building, and institutional support are required to optimize its implementation.